Realisme Sosial sebagai Mazhab Sastra Arab - Habib Al-amien (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
The school of Socialist Realism in literature is a part of the realism movement that emerged last. The purpose of this research is to examine the development of the Socialist Realism school and its reflection in Arabic literature. The research method employed is a descriptive qualitative and bibliographic approach. The data sources utilized include books and articles discussing Socialist Realism, as well as Arabic literary works such as Auda' wa Tsu'ban and Aulad Hatiina by Qissah Rifa'ah. The findings of this research reveal two main orientations within the Socialist Realism literary school: (1) a strong adherence to Marxism, and (2) a focus on the concept of social classes as a means to advocate for social justice.